Soluble urokinase plasminogen activator receptor is compartmentally regulated in decompensated cirrhosis and indicates immune activation and short‐term mortality. (17th March 2013) - Zimmermann, H. W.; Reuken, P. A.; Koch, A.; Bartneck, M.; Adams, D. H.; Trautwein, C.; Stallmach, A.; Tacke, F.; Bruns, T.
Abstract Objective Patients with decompensated cirrhosis are susceptible to bacterial infections, which are associated with organ failure and a high mortality rate. Reliable biomarkers are needed to identify patients who require intensified treatment. Our objective was to study the regulation and prognostic relevance of elevated concentrations of soluble urokinase plasminogen activator receptor (suPAR) in patients with advanced cirrhosis. Design, setting and participants We examined the associations between serum and ascitic fluid (AF) suPAR and liver function, bacterial infection, and short‐term mortality in 162 consecutive patients with decompensated cirrhosis undergoing diagnostic paracentesis in a tertiary health care centre in Germany. Main outcome measure Twenty‐eight‐day mortality. Results Circulating suPAR levels were increased in patients with decompensated cirrhosis and correlated with the severity of liver dysfunction and systemic inflammation but were not indicative of bacterial infection. Circulating suPAR levels >14.4 ng mL−1 predicted 28‐day mortality, even after adjustment for liver function and confounders [HR = 3.05 (1.35–6.90); P = 0.0076] equal to the MELD score (AUC = 0.71; 95% CI = 0.61–0.81; P < 0.001). Cut‐off levels derived from cohorts without liver disease were not applicable due to the low specificity. AF suPAR levels were elevated during spontaneous bacterial peritonitis (SBP), but not during episodes in which bacteria or bacterial DNA was translocated into the ascites. AF suPAR levels correlated poorly with systemic suPAR but were associated with a more severe course of SBP and a worse outcome. In vitro experiments revealed that monocytes, and to a lesser extent neutrophils, secrete suPAR after Toll‐like‐receptor ligation, which led to rapid urokinase plasminogen activator receptor cleavage followed by increased synthesis. Conclusion Blood and ascitic suPAR levels provide distinct, but relevant prognostic information on the severity of complications in patients with end‐stage liver disease.